Development and characterisation of paracetamol honey suspension - Muhammad Salahuddin bin Haris @ Harith (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Paracetamol (PCM) is a common analgesic and antipyretic drug used worldwide which is available in various dosage forms such as tablet, capsule, suppository, syrup and suspension. PCM suspension available in the market contains high amount of sugar to mask the bitter taste of PCM. High sucrose content will lead to health problems such as dental caries especially in children who frequently have fever and colds. This study aimed to explore the potential of honey to substitute sugar in PCM suspension. Honey is widely known as a natural sweetener. Besides, it contains micronutrients such as vitamins and enzymes that give a wholesome benefit such as antibacterial and antifungal properties. Compatibility study was performed on the API and its binary mixture with excipient using differential scanning calorimetry (DSC) and supported by attenuated total reflectance (ATR). DSC results showed incompatibility between PCM and parabens where the melting peak of PCM disappeared. However, ATR spectra of those combinations excluded these incompatibilities. Preliminary lab scale of paracetamol honey suspension (PHS) for 2 L was done with the incorporation of colloid mill for 10 minutes. The lab scale PHS had 689.2 ± 50.8 nm particle size, 0.518 ± 0.051 span, -47.76 ± 1.20 mV zeta potential, 5.36 ± 0.04 pH and 692.6 ± 7.5 mPa.s viscosity. These characteristics were similar to the Panadol® suspension. Analgesic and antipyretic activities of the suspension compared against Panadol® were also performed on Sprague-Dawley rats using hot plate method and Brewer's yeast-induced pyrexia model respectively. PHS had prolonged analgesic activity up to 180 minutes compared to Panadol® suspension which was 120 minutes. PHS had similar antipyretic activity with Panadol® suspension. Analytical methods verification (AMV) of PHS including specificity, peak purity, linearity, limit of detection (LOD), limit of quantification (LOQ) and intermediate precision was performed using HPLC. Besides, AMV of 4-aminophenol including specificity, peak purity, LOD and LOQ was also performed. All the AMV parameters met all the compendial specifications. PHS was scaled-up to 500 liters to identify optimum processing parameters such as mixing time, mixing speed, milling gap size and milling time. Based on scale-up results, milling gap size and time significantly (p<0.05) reduce particle size, polydispersity index (PdI), zeta potential and viscosity of the suspension. Samples from scale-up process were taken and stored in both real time and accelerated stability chambers for stability study. All stability study characteristics including appearance, assay, 4-aminophenol content, pH, total aerobic microbial count (TAMC), total yeasts and moulds count (TYMC), absence of E. coli at all-time points met all the compendial specifications except for appearance of the suspension at 6-month accelerated stability point which was more brownish due to honey that underwent Maillard reaction. Once the optimum processing parameters were identified, process validation (PV) was conducted and subjected to the same characterisations as the scale-up PHS. The PHS was successfully manufactured for commercialisation. In conclusion, the PHS was successfully manufactured for this pre-commercialisation stage. The suspension met all the compendial specification and is regarded as safe, effective and of good quality.